The Role of Information Technology as Mediating Variable of Professionalism and Competence in Auditor Performance - Dian Indudewi; Yosi Feronika (Quantitative Economics and Management Studies, 2023)
Large-Scale Social Restrictions (PSBB) in Indonesia have changed how all professions work, including auditors. PSBB situation has led to auditors needing to identify relevant changes to auditors' ability to obtain sufficient and appropriate audit evidence during the pandemic. Information technology is beneficial for auditors during the completion of audit work. This research aims to determine the influence of information technology in mediating professionalism and competence on auditor performance during the Covid-19 pandemic at the Public Accounting Firm in Semarang City. This study used primary data from questionnaires. One hundred and nineteen questionnaires were distributed to seventeen public accounting firms in Semarang, and ninety-one questionnaires can be processed. This study used SEM PLS 3.0 for calculating and analyzing data. The validity and reliability test results show that the indicator is worth using. The results showed that information technology and professionalism significantly affected auditor performance during the Covid-19 pandemic, while competence did not affect auditor performance during the Covid-19 pandemic. Information technology mediates in a complementary manner the influence of professionalism on the performance of auditors. Information technology fully mediates the influence of competence on auditor performance.